Preparation method of high-conductivity antimony-doped lithium iron phosphate positive electrode material

By doping acidified antimony into the lithium iron phosphate positive electrode material, the synergistic effect of antimony and lithium is used to improve the conductivity, and the specific surface area is increased through high-temperature calcination, the problem of insufficient conductivity of the positive electrode material of lithium iron phosphate battery is solved, and the performance of lithium ion batteries is significantly improved.

CN119591069APending Publication Date: 2025-03-11HUBEI XINGFA CHEM GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411362038.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing lithium iron phosphate battery positive electrode materials have shortcomings in terms of electrical conductivity, which limits the working voltage and battery capacity of lithium-ion batteries.

Method used

The preparation method of acidified antimony-doped lithium iron phosphate positive electrode material is adopted. Through the synergistic action of antimony and lithium, the electronic guide belt of metal lithium is increased, the conductivity of the material is enhanced, and the specific surface area of ​​the material is increased through high-temperature calcination, thereby reducing the charge transfer impedance.

Benefits of technology

The conductivity and electrochemical performance of antimony-doped lithium iron phosphate positive electrode material is significantly improved, and the working voltage and battery capacity of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591069A_ABST
    Figure CN119591069A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of new energy storage batteries, and relates to a preparation method of a high-conductivity antimony-doped lithium iron phosphate positive electrode material, which comprises the following steps: 1, mixing and stirring a certain amount of antimony source and a phosphoric acid solution to obtain an acidified antimony source solution A; 2, carrying out hydrothermal reaction on the solution A, and washing to obtain an antimony-phosphorus product; 3, mixing and stirring the lithium source solution B and the antimony-phosphorus product to form a solution C; 4, mixing the solution C, a carbon source, iron phosphate and deionized water into slurry; 5, sanding the obtained slurry to a certain particle size, and then carrying out spray drying; and 6, calcining the dried lithium iron phosphate in an inert gas atmosphere, cooling to room temperature, and crushing and sieving the material to obtain the antimony-doped lithium iron phosphate material. The electrode material prepared by the method provided by the invention can be applied to a positive electrode material of a battery, and the antimony-doped lithium iron phosphate positive electrode material has proper specific surface area and high conductivity, so that the electrochemical performance of the positive electrode material is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a positive electrode material of a lithium-ion battery in the field of new energy storage batteries, and in particular to a method for preparing a highly conductive antimony-doped lithium iron phosphate positive electrode material and application thereof. Background Art

[0002] New energy vehicles have been vigorously developed. However, whether it is a pure electric vehicle or a hybrid vehicle, its core component is the power battery. Among them, lithium-ion batteries have been widely studied and applied due to their own battery performance, price and safety. As the core component of lithium-ion batteries, the improvement of the performance of the positive electrode material will largely determine the improvement of the performance of the entire lithium-ion battery. Among them, LiFePO4 materials have particularly outstanding performance in terms of stable electrical properties, long cycle life and green environmental protection, and have quickly entered the field of vision of new energy companies. However, the low electronic conductivity of LiFePO4 materials limits its large-scale production and application in the field of lithium-ion power batteries. In order to improve the conductivity of LiFePO4 and increase the operating voltage of lithium-ion batteries, many researchers have proposed to dope antimony at the oxygen position in LiFePO4 to obtain antimony-doped lithium iron phosphate positive electrode materials. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing an acidified antimony-doped lithium iron phosphate positive electrode material with a simple synthesis process and significantly enhanced conductivity effect, in view of the shortcomings of the current lithium iron phosphate battery positive electrode material in terms of conductivity. The synthesis process of the electrode material prepared by the method is simple, and the doped antimony and lithium have a synergistic effect, which promotes the electron conduction band transition of metallic lithium and improves the conductivity of the material. In addition, during the high-temperature calcination process, due to the volatile nature of antimony, the specific surface area of ​​the material is increased to a suitable range, thereby reducing the charge transfer impedance of the material and improving the battery capacity.

[0004] The present invention provides an antimony-doped lithium iron phosphate positive electrode material with outstanding conductivity. The antimony-doped lithium iron phosphate material exhibits excellent physical and chemical properties, has a particle size of 1.0 μm to 2.0 μm, has a suitable specific surface area and high conductivity, and has outstanding electrochemical performance.

[0005] The present invention provides a highly conductive antimony-doped lithium iron phosphate positive electrode material, and the specific synthesis scheme is as follows: (1) mixing an antimony source and a phosphoric acid solution and stirring to form a solution A; (2) Solution A is subjected to a hydrothermal reaction and then washed with water to obtain an antimony-phosphorus product; (3) mixing the lithium source solution B and the antimony-phosphorus product and stirring to form a solution C; (4) mixing solution C, a carbon source, iron phosphate and deionized water into slurry S1; (5) grinding the slurry S1 to a certain particle size, and then spray drying it to obtain a lithium iron phosphate precursor S2; (6) The dried lithium iron phosphate precursor S2 is calcined in an inert gas atmosphere, and after cooling to room temperature, the material is crushed and sieved to obtain an antimony-doped lithium iron phosphate material.

[0006] Specifically, the antimony source in step (1) is at least one of SbCl3, SbBr3, SbF3, Sb2Br3 and antimony oxalate.

[0007] The mass concentration of the phosphoric acid solution in step (1) is 70-90%.

[0008] In step (2), the antimony source and the phosphoric acid solution are mixed and reacted in an autoclave at 140-180° C. for 2-3 hours.

[0009] Specifically, the lithium source in step (3) is at least one of Li2CO3, LiBr, Li2HPO4, LiH2PO4, LiOH and LiHCO3.

[0010] Specifically, the carbon source in step (4) is one of citric acid, glucose, sucrose, vinyl alcohol, urea, and oxalic acid, or a combination of any of them.

[0011] Specifically, the iron phosphate particle size D50 in step (4) is 5 μm-20 μm.

[0012] Specifically, in step (4), the molar ratio of iron in the ferric phosphate to carbon in the carbon source is 1:0.2-0.6, and the molar ratio of iron in the ferric phosphate to antimony in the antimony source is 1:0.001-0.01.

[0013] Specifically, the slurry in step (5) is sand-milled to a particle size D50 of 250 nm-300 nm.

[0014] Specifically, in step (6), the calcination temperature is 700-900°C, and the holding time is 3-6 h; the inert atmosphere is nitrogen or argon.

[0015] Compared with the existing lithium iron phosphate preparation technology, the beneficial effects of the present invention are: 1. Acidified antimony is used for doping, and no other organic solvents and dispersants need to be added. The method is novel, unique, efficient and environmentally friendly.

[0016] 2. The required materials are synthesized by gas phase method, the process is simple and the effect is obvious.

[0017] 3. The doped antimony and lithium have a synergistic effect, which promotes the electron migration of metallic lithium to the conduction band and improves the electrical conductivity of the material.

[0018] 4. During the high-temperature calcination process, antimony, due to its volatile nature, causes the specific surface area of ​​the material to increase to an appropriate range, thereby reducing the charge transfer impedance of the material and increasing the battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the electrochemical impedance spectroscopy (EIS) of the antimony-doped lithium iron phosphate positive electrode material prepared in Example 1 of the present invention, and the inset is an equivalent circuit diagram. s Represents the equivalent series resistance, including the intrinsic internal resistance of the active material, the electrolyte solution resistance and the contact resistance; R ct It represents the charge transfer resistance, which indicates the ease with which the electrochemical reaction proceeds and is related to the movement of ions at the interface between the active material and the electrolyte. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with the embodiments. It should also be understood that the following embodiments are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. The specific quality, reaction time and temperature, process parameters, etc. in the examples are only examples within the appropriate ranges. Some non-essential improvements and adjustments made by those skilled in the art according to the above content of the present invention all belong to the scope of protection of the present invention.

[0021] Example 1 Preparation of electrode materials: 250 g of iron phosphate and 1.4410 g of antimony trichloride were weighed according to a molar ratio of 1:0.004 between iron in iron phosphate and antimony in antimony trichloride, wherein antimony trichloride was mixed with 70% by mass phosphoric acid solution to form solution A, which was reacted in a closed polytetrafluoroethylene reactor at 150°C for 2 h to obtain an antimony-phosphorus product after washing with water; lithium carbonate (90 g) was mixed with deionized water to form solution B; the antimony-phosphorus product was mixed with solution B to form solution C. According to the molar ratio of iron in iron phosphate to carbon in glucose of 1:0.4 (250 g of iron phosphate), 18.96 g of glucose was weighed, mixed with solution C, iron phosphate and deionized water, and stirred into a uniform slurry S1. The slurry was sand-milled to a particle size D50 of 250 nm-300 nm; the sand-milled slurry was spray-dried, and the dried lithium iron phosphate precursor S2 was calcined at 800 °C in an argon atmosphere for 9 h. After cooling to room temperature, the material was crushed and sieved to obtain antimony-doped lithium iron phosphate material.

[0022] Evaluation of electrode material performance: The specific surface area and powder resistivity of antimony-doped lithium iron phosphate powder were tested. The antimony-doped lithium iron phosphate powder was assembled into a CR2032 button battery at a ratio of 95% of active material, and the electrochemical properties of the button battery were tested, including battery internal resistance, EIS impedance, and gram capacity. The data results are shown in Table 1.

[0023] Example 2 Preparation of electrode materials: 250 g of iron phosphate and 0.3602 g of antimony trichloride were weighed according to a molar ratio of 1:0.001 between iron in iron phosphate and antimony in antimony trichloride, wherein antimony trichloride was mixed with 70% by mass of phosphoric acid solution to form solution A; the mixture was sealed and reacted in a polytetrafluoroethylene reactor at 150°C for 2 h, and the product was washed with water to obtain an antimony-phosphorus product; lithium carbonate (90 g) was mixed with deionized water to form solution B; the antimony-phosphorus product was mixed with solution B to form solution C. According to the molar ratio of iron in iron phosphate to carbon in glucose of 1:0.4 (250 g of iron phosphate), 18.96 g of glucose was weighed, mixed with solution C, iron phosphate and deionized water, and stirred into a uniform slurry S1. The slurry was sand-milled to a particle size D50 of 250 nm-300 nm; the sand-milled slurry was spray-dried, and the dried lithium iron phosphate precursor S2 was calcined at 800 °C in an argon atmosphere for 9 h. After cooling to room temperature, the material was crushed and sieved to obtain antimony-doped lithium iron phosphate material.

[0024] Evaluation of electrode material performance: Detect the specific surface area and powder resistivity of antimony-doped lithium iron phosphate powder; assemble CR2032 button batteries with antimony-doped lithium iron phosphate powder at a ratio of 95% of active material, and detect the electrochemical performance of button batteries, including battery internal resistance, EIS impedance, and gram capacity. The data results are shown in Table 1.

[0025] Example 3 Preparation of electrode materials: 250 g of iron phosphate and 1.4410 g of antimony trichloride were weighed according to a molar ratio of 1:0.004 between iron in iron phosphate and antimony in antimony trichloride, wherein antimony trichloride was mixed with 80% by mass of phosphoric acid solution to form solution A; the mixture was sealed and reacted in a polytetrafluoroethylene reactor at 150°C for 2 h, and the product was washed with water to obtain an antimony-phosphorus product; lithium carbonate (90 g) was mixed with deionized water to form solution B; the antimony-phosphorus product was mixed with solution B to form solution C. According to the molar ratio of iron in iron phosphate to carbon in glucose of 1:0.4 (250 g of iron phosphate), 18.96 g of glucose was weighed, mixed with solution C, iron phosphate and deionized water, and stirred into a uniform slurry S1. The slurry was sand-milled to a particle size D50 of 250 nm-300 nm; the sand-milled slurry was spray-dried, and the dried lithium iron phosphate precursor S2 was calcined at 800 °C in an argon atmosphere for 9 h. After cooling to room temperature, the material was crushed and sieved to obtain antimony-doped lithium iron phosphate material.

[0026] Evaluation of electrode material performance: Detect the specific surface area and powder resistivity of antimony-doped lithium iron phosphate powder; assemble CR2032 button batteries with antimony-doped lithium iron phosphate powder at a ratio of 95% of active material, and detect the electrochemical performance of button batteries, including battery internal resistance, EIS impedance, and gram capacity. The data results are shown in Table 1.

[0027] Example 4 Preparation of electrode materials: 250 g of iron phosphate and 1.4410 g of antimony trichloride were weighed according to a molar ratio of 1:0.004 between iron in iron phosphate and antimony in antimony trichloride, wherein antimony trichloride was mixed with 90% by mass of phosphoric acid solution to form solution A; the mixture was sealed and reacted in a polytetrafluoroethylene reactor at 150°C for 2 h, and the product was washed with water to obtain an antimony-phosphorus product; lithium carbonate (90 g) was mixed with deionized water to form solution B; the antimony-phosphorus product was mixed with solution B to form solution C. According to the molar ratio of iron in iron phosphate to carbon in glucose of 1:0.4 (250 g of iron phosphate), 18.96 g of glucose was weighed, mixed with solution C, iron phosphate and deionized water, and stirred into a uniform slurry S1. The slurry was sand-milled to a particle size D50 of 250 nm-300 nm; the sand-milled slurry was spray-dried, and the dried lithium iron phosphate precursor S2 was calcined at 800 °C in an argon atmosphere for 9 h. After cooling to room temperature, the material was crushed and sieved to obtain antimony-doped lithium iron phosphate material.

[0028] Evaluation of electrode material performance: Detect the specific surface area and powder resistivity of antimony-doped lithium iron phosphate powder; assemble CR2032 button batteries with antimony-doped lithium iron phosphate powder at a ratio of 95% of active material, and detect the electrochemical performance of button batteries, including battery internal resistance, EIS impedance, and gram capacity. The data results are shown in Table 1.

[0029] Example 5 Preparation of electrode materials: According to the molar ratio of iron in iron phosphate to carbon in glucose of 1:0.4, 250 g of iron phosphate and 18.96 g of glucose were weighed, mixed with deionized water, and stirred into a uniform slurry. The slurry was sand-milled to a particle size D50 of 250 nm-300 nm. The sand-milled slurry was spray-dried, and the dried lithium iron phosphate was calcined at 800°C for 9 h in an argon atmosphere. After cooling to room temperature, the material was crushed and sieved to obtain lithium iron phosphate material.

[0030] Evaluation of electrode material performance: Detect the specific surface area and powder resistivity of antimony-doped lithium iron phosphate powder; assemble CR2032 button batteries with antimony-doped lithium iron phosphate powder at a ratio of 95% of active material, and detect the electrochemical performance of button batteries, including battery internal resistance, EIS impedance, and gram capacity. The data results are shown in Table 1.

[0031] Example 6 Preparation of electrode materials: 250 g of iron phosphate and 36.02 g of antimony trichloride were weighed according to the molar ratio of iron in iron phosphate to antimony in antimony trichloride of 1:0.004, wherein antimony trichloride was mixed with 60% by mass fraction of phosphoric acid solution to form solution A; the reaction was carried out in a closed polytetrafluoroethylene reactor at 150°C for 2 hours, and the product was washed with water to obtain an antimony-phosphorus product; lithium carbonate (90 g) was mixed with deionized water to form solution B; the antimony-phosphorus product was mixed with solution B to form solution C. According to the molar ratio of iron in iron phosphate to carbon in glucose of 1:0.4 (250 g of iron phosphate), 18.96 g of glucose was weighed, mixed with solution C, iron phosphate and deionized water, and stirred into a uniform slurry S1. The slurry was sand-milled to a particle size D50 of 250 nm-300 nm; the sand-milled slurry was spray-dried, and the dried lithium iron phosphate precursor S2 was calcined at 800 °C in an argon atmosphere for 9 h. After cooling to room temperature, the material was crushed and sieved to obtain antimony-doped lithium iron phosphate material.

[0032] Evaluation of electrode material performance: Detect the specific surface area and powder resistivity of antimony-doped lithium iron phosphate powder; assemble CR2032 button batteries with antimony-doped lithium iron phosphate powder at a ratio of 95% of active material, and detect the electrochemical performance of button batteries, including battery internal resistance, EIS impedance, and gram capacity. The data results are shown in Table 1.

[0033] Example 7 Preparation of electrode materials: 250 g of iron phosphate and 0.92 g of antimony trioxide were weighed according to the molar ratio of iron in iron phosphate to antimony in antimony trichloride of 1:0.004, wherein antimony trioxide was mixed with the aqueous solution and stirred to form solution A; the reaction was carried out in a closed polytetrafluoroethylene reactor at 150°C for 2 hours, and the product was washed with water to obtain a hydrothermal product of antimony; lithium carbonate (90 g) was mixed with deionized water and stirred to form solution B; the hydrothermal product of antimony was mixed with solution B and stirred to form solution C. According to the molar ratio of iron in iron phosphate to carbon in glucose of 1:0.4 (250 g of iron phosphate), 18.96 g of glucose was weighed, mixed with solution C, iron phosphate and deionized water, and stirred into a uniform slurry S1. The slurry was sand-milled to a particle size D50 of 250 nm-300 nm; the sand-milled slurry was spray-dried, and the dried lithium iron phosphate precursor S2 was calcined at 800 °C in an argon atmosphere for 9 h. After cooling to room temperature, the material was crushed and sieved to obtain antimony-doped lithium iron phosphate material.

[0034] Evaluation of electrode material performance: Detect the specific surface area and powder resistivity of antimony-doped lithium iron phosphate powder; assemble CR2032 button batteries with antimony-doped lithium iron phosphate powder at a ratio of 95% of active material, and detect the electrochemical performance of button batteries, including battery internal resistance, EIS impedance, and gram capacity. The data results are shown in Table 1.

[0035] Example 8 Preparation of electrode materials: 250 g of iron phosphate and 1.60 g of antimony oxalate were weighed according to the molar ratio of iron in iron phosphate to antimony in antimony trichloride of 1:0.004, wherein antimony oxalate was mixed with 30% by mass fraction of phosphoric acid to form solution A, and the mixture was reacted in a closed polytetrafluoroethylene reactor at 150°C for 2 h. The product was washed with water to obtain an antimony-phosphorus product; lithium carbonate (90 g) was mixed with deionized water to form solution B; the antimony-phosphorus product was mixed with solution B to form solution C. According to the molar ratio of iron in iron phosphate to carbon in glucose of 1:0.4 (250 g of iron phosphate), 18.96 g of glucose was weighed, mixed with solution C, iron phosphate and deionized water, and stirred into a uniform slurry S1. The slurry was sand-milled to a particle size D50 of 250 nm-300 nm; the sand-milled slurry was spray-dried, and the dried lithium iron phosphate precursor S2 was calcined at 800 °C in an argon atmosphere for 9 h. After cooling to room temperature, the material was crushed and sieved to obtain antimony-doped lithium iron phosphate material.

[0036] Evaluation of electrode material performance: Detect the specific surface area and powder resistivity of antimony-doped lithium iron phosphate powder; assemble CR2032 button batteries with antimony-doped lithium iron phosphate powder at a ratio of 95% of active material, and detect the electrochemical performance of button batteries, including battery internal resistance, EIS impedance, and gram capacity. The data results are shown in Table 1.

[0037] Table 1 Electrode material performance evaluation data

[0038] 1. Table 1 shows the performance data of the antimony-doped lithium iron phosphate materials prepared in various embodiments and comparative examples, including specific surface area, powder resistivity, battery internal resistance, EIS impedance and 0.1C discharge specific capacity.

[0039] 2. By comparison, it can be seen that Example 1 has a greater 0.1C discharge capacity than the other examples and comparative examples, which is mainly due to its powder resistivity and EIS impedance being smaller than the other examples. The smaller powder resistivity and EIS impedance are due to the fact that Example 1 has the most suitable specific surface area, which reduces the charge transfer impedance of the material and improves the conductive properties of the material.

Claims

1. A method for preparing a highly conductive antimony-doped lithium iron phosphate positive electrode material, characterized in that: The preparation steps are as follows: (1) mixing an antimony source and a phosphoric acid solution and stirring to form a solution A; (2) Solution A is subjected to a hydrothermal reaction and then washed with water to obtain an antimony-phosphorus product; (3) mixing the lithium source solution B and the antimony-phosphorus product and stirring to form a solution C; (4) mixing solution C, carbon source, iron phosphate and deionized water into slurry S1; (5) grinding the slurry S1 to a certain particle size, and then spray drying it to obtain a lithium iron phosphate precursor S2; (6) The dried lithium iron phosphate precursor S2 is calcined in an inert gas atmosphere, and after cooling to room temperature, the material is crushed and sieved to obtain an antimony-doped lithium iron phosphate material.

2. The preparation method according to claim 1, characterized in that: The antimony source in step (1) is at least one of SbCl3, SbBr3, SbF3, Sb2Br3 and antimony oxalate.

3. The preparation method according to claim 2, characterized in that: The mass concentration of the phosphoric acid solution in step (1) is 70-90%.

4. The preparation method according to claim 3, characterized in that: In step (2), the antimony source and the phosphoric acid solution are mixed and reacted in an autoclave at 140-180° C. for 2-3 hours.

5. The preparation method according to claim 1, characterized in that: The lithium source in step (3) is at least one of Li2CO3, LiBr, Li2HPO4, LiH2PO4, LiOH and LiHCO3.

6. The preparation method according to claim 1, characterized in that: The carbon source in step (4) is one of citric acid, glucose, sucrose, vinyl alcohol, urea, and oxalic acid, or a combination of any of them.

7. The preparation method according to claim 1, characterized in that The particle size D50 of the iron phosphate in step (4) is 5 μm-20 μm; the molar ratio of iron in the iron phosphate to carbon in the carbon source is 1:0.2-0.6, and the molar ratio of iron in the iron phosphate to antimony in the antimony source is 1:0.001-0.

01.

8. The preparation method according to claim 1, characterized in that The slurry in step (5) is sand-milled to a particle size D50 of 250 nm-300 nm.

9. The preparation method according to claim 1, characterized in that In step (6), the calcination temperature is 700-900° C., and the holding time is 3-6 h; the inert atmosphere is nitrogen or argon.

10. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the method according to any one of claims 1 to 9.